A simple method for extraction and purification of pedunculoside from the dried barks of Ilex rotunda and its inhibitory effect on pancreatic lipase in vitro. Issue 18 (12th December 2017) - Yan, Zenghao; Su, Minmin; Pan, Wenjun; Su, Weiwei; Wang, Yonggang
ABSTRACT: A simple and efficient method was developed for the preparation of pedunculoside from the dried barks of Ilex rotunda . Pedunculoside was extracted by heat reflux. The optimal conditions were determined by the response surface methodology (40% ethanol concentration, 14 mL/g solvent/material loading level and 90 min extraction time with the dried barks being extracted twice). After extraction and condensing the crude extract, pedunculoside was directly purified through crystallization in water with the addition of ethyl acetate. Pedunculoside (96.9% purity) was obtained with 48.2% recovery after the extraction and purification. Compared with the reported chromatographic methods, this strategy is simple, eco-friendly, and economical. The purified pedunculoside showed an inhibitory effect on pancreatic lipase in vitro (IC50 = 80.8 μg/mL), suggesting its anti-obesity potential.